2019
DOI: 10.3390/agronomy9090540
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mobile Heat Treatment System for Treating In-Field HLB-Affected Trees by Analyzing Survival Rate of Surrogate Bacteria

Abstract: Huanglongbing (HLB or citrus greening) is a disease caused by an insect-transmitted bacterial pathogen Candidatus Liberibacter asiaticus (CLas). Thermotherapy has been successfully used by others to reduce the population of CLas bacteria in HLB-affected citrus trees under greenhouse studies. Thermotherapy is the application of heat as a strategy to reduce the adverse economic impact of certain pests and diseases. CLas is a fastidious, non-cultivable organism. The high variance in CLas titers in canopy samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Such qPCR negative results are typical for hot summer months, as the bacteria clears in the shoots due to high temperatures, which were in the range of 100-120 °F during May-August. Although well-documented, this problem substantially complicates qPCR-based diagnostics of HLB [31][32][33][34] . The Raman readings, however, reported stable signal intensity of 1610 cm −1 band above 1.925 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such qPCR negative results are typical for hot summer months, as the bacteria clears in the shoots due to high temperatures, which were in the range of 100-120 °F during May-August. Although well-documented, this problem substantially complicates qPCR-based diagnostics of HLB [31][32][33][34] . The Raman readings, however, reported stable signal intensity of 1610 cm −1 band above 1.925 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MHTS was also evaluated in the field by using a bio-based sensor (a surrogate bacterium, Klebsiella oxytoca). It was reported that the system showed good killing efficiency (3.35 log reductions in colony-forming units to the complete elimination of the bacteria) at a raised maximum temperature of 54 °C for 250 s [ 264 ]. Therefore, thermotherapy treatment could be one of the effective control strategies in an integrated management of HLB.…”
Section: Triangular Management Strategiesmentioning
confidence: 99%
“…Currently, many strategies have been developed for HLB mitigation, including application of antimicrobials ( Zhang et al, 2011a , 2012 , 2014 , 2021 ; Hu and Wang, 2016 ; Hu et al, 2018 ; Yang et al, 2018 ), thermotherapy ( Hoffman et al, 2013 ; Fan et al, 2016 ; Yang et al, 2016b ; Doud et al, 2017 ; Ghatrehsamani et al, 2019 ; Vincent et al, 2019 ), macro-and micronutrients ( Spann and Schumann, 2009 ; Gottwald et al, 2012 ; Rouse et al, 2017 ; Mattos-Jr et al, 2020 ; Dong et al, 2021 ; Zhou et al, 2021 ), plant defense inducers ( Canales et al, 2016 ; Li et al, 2016 , 2019 , 2021a ; Hu et al, 2018 ; Wang, 2021 ), control of the insect vector ( Grafton-Cardwell et al, 2013 ; Boina and Bloomquist, 2015 ; Cocuzza et al, 2017 ; Pierre et al, 2021 ), biocontrol ( Trivedi et al, 2011 ; Hopkins and Wall, 2021 ; Nan et al, 2021 ; Poveda et al, 2021 ), and eradication of HLB symptomatic citrus trees ( Bassanezi et al, 2013 ; Yuan et al, 2020 ). However, these strategies have shown limited success in field applications and effective HLB management remains a challenge.…”
Section: Introductionmentioning
confidence: 99%